Peran Aktualisasi Diri sebagai Intervening Keteladanan dan Komunikasi Pimpinan terhadap Kinerja Pegawai - Supriatal, Supriatal; Mulyanto, Heru (Jurnal Manajemen Bisnis dan Keuangan, 2023)
This research aims to evaluate the role of self-actualization as an intermediary in the influence of leadership example and communication on employee performance at Bina Mandiri Multimedia Vocational School. The exemplary variable is understood through three indicators, namely exemplifying the method, inspiring, and challenging the process. The leader communication variable also has two indicators, namely verbal and non-verbal communication. Meanwhile, self-actualization is understood through indicators such as the search for happiness, achieving personal success, and understanding one's identity. Performance variables are defined through aspects such as quality, quantity, and responsibility. This research uses quantitative methods with a confidence level of 95%. The sample used consisted of all employees of Bina Mandiri Multimedia Vocational School, namely 40 people. The data collection method involves the use of primary data through observation and questionnaires and secondary data through literature study. The research instrument was tested through validity and reliability tests. Data analysis was carried out using Smart PLS with a partial square structural analysis approach. The research results show that leadership example has a positive impact on self-actualization which in turn has a positive and significant effect on employee performance. Meanwhile, leadership communication has a smaller or insignificant impact on self-actualization and its influence on employee performance is also limited through this factor.